Improved Neural Control of Movements Manifests in Expertise-Related Differences in Force Output and Brain Network Dynamics - Gölz, Christian; Voelcker-Rehage, Claudia; Mora, Karin; Reuter, Eva-Maria; Godde, Ben; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Frontiers in Physiology, 2018)
It is well-established that expertise, developed through continuous and deliberate practice, has the potential to delay age-related decline in fine motor skills. However, less is known about underlying mechanisms, i.e., whether expertise leads to a higher performance level changing the initial status from which age-related decline starts or if expertise-related changes result in qualitatively different motor output and neural processing providing a resource of compensation for age-related changes. Thus, as a first step, this study aimed at a better understanding of expertise-related changes in fine motor control with respect to force output and respective electrophysiological correlates. Here, using a multidimensional approach, we investigated fine motor control of experts and novices in precision mechanics during execution of a dynamic force control task. On the level of force output, we analyzed precision, variability and complexity. We further used dynamic mode decomposition (DMD) to analyze the electrophysiological correlates of force control to deduce brain network dynamics. Experts’ force output was more precise, less variable, and more complex. Task-related DMD mean mode magnitudes within the α-band at electrodes over sensorimotor relevant areas were reduced in experts and lower DMD mean mode magnitudes related to the force output in novices. Our results provide evidence for expertise dependent central adaptions with distinct and more complex organization and decentralization of sensorimotor subsystems. Results from our multidimensional approach can be seen as a step forward in understanding expertise-related changes and exploiting their potential as resources for healthy ageing. variable, and more complex. Besides, we detected lower task related DMD mode magnitudes within the α-band at electrodes over sensorimotor relevant areas. These results provide evidence for expertise dependent central adaptions with distinct organization and decentralization of sensorimotor subsystems. Viewed in the context of lifespan research, this illustrates the potential of deliberate practice to influence the development of specific competences.